A Case Report of Anaphylactic Shock Induced by Cisatracurium - XiaYao; Wang, Jing; Liu, Baichen; Rong, Xiaoli; Wang, Baohua (Archives of Clinical and Medical Case Reports, 2019)
We report a case of severe anaphylactic shock caused by cisatracurium, a 30-year-old female who prepared to undergo cervical conization and had a history of penicillin allergy. Severe cardiovascular collapse suddenly occurred after giving the general anesthetic induction drugs (midazolam, fentanyl, propofol, and cisatracurium). Then, the patient received anti-anaphylactic shock therapy. The rescue was successful, but her surgery was cancelled. An allergen skin test was performed after 6 weeks, the results showed that cisatracurium was positive and confirmed that the allergic shock was caused by cisatracurium. In order to avoid the use of cisatracurium, the subsequent surgery was not performed with general anesthesia, instead of epidural anesthesia. The anesthesia was performed smoothly and the patient returned to the ward safely.